Successful treatment of extensively drug-resistant Acinetobacter baumannii ventriculitis with polymyxin B and tigecycline- a case report - Wei Guo (Antimicrobial Resistance and Infection Control, 2018)
Abstract Background Acinetobacter baumannii nosocomial ventriculitis/meningitis, especially those due to drug-resistant strains, has substantially increased over recent years. However, limited therapeutic options exist for the Acinetobacter baumannii ventriculitis/meningitis because of the poor penetration rate of most antibiotics through the blood-brain barrier. Case presentation A 57-year-old male patient developed ventriculitis from an extensively drug-resistant strain of Acinetobacter baumannii after the decompressive craniectomy for severe traumatic brain injury. The patient was successfully treated with intraventricular and intravenous polymyxin B together with intravenous tigecycline. Conclusions The case illustrates intraventricular polymyxin B can be a therapeutic option against extensively drug-resistant Acinetobacter baumannii ventriculitis.